'Divinity, Adieu!' The Modern Subject and the Encounter with Scripture in Christopher Marlowe'sDoctor Faustus. (3rd March 2018) - DeCook, Travis
Abstract: Throughout Marlowe's tragedy Doctor Faustus, the protagonist experiences the Bible and individual scriptural passages as uncannily divorced from their divine source, and therefore available to be comprehensively judged and dismissed from the vantage point of a sovereign subjectivity. This construction of the Bible is bound up with both the autonomy Faustus imagines for himself, and with his secular view of the world, in which entities possess their being in a self-contained and self-grounding manner, and are therefore available to his full comprehension and control. This article concludes by considering how we might account for the apparent convergence of Faustus's construction of Scripture and modern theories of Protestant biblicism.